2021
DOI: 10.1093/jac/dkab292
|View full text |Cite
|
Sign up to set email alerts
|

Aztreonam/avibactam effect on pharmacodynamic indices for mutant selection ofEscherichia coli and Klebsiella pneumoniaeharbouring serine- and New Delhi metallo-β-lactamases

Abstract: Objectives Ceftazidime/avibactam is not active against MBL-producing bacteria. Combining ceftazidime/avibactam or avibactam with aztreonam can counter the resistance of MBL-producing Enterobacterales. The aim of this study was to evaluate whether the addition of avibactam could reduce or close the mutant selection window (MSW) of aztreonam in Escherichia coli and Klebsiella pneumoniae harbouring MBLs; MSW is a pharmacodynamic (PD) parameter for the selection of emergent resistant mutants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The clinical isolates were provided by Dr. Yuanqi Zhu. Next-generation sequencing was used to determine the resistance genes in each isolate, as described ( Feng et al, 2021 ). Eleven clinical A. baumannii strains harboring bla OXA-23 were selected.…”
Section: Methodsmentioning
confidence: 99%
“…The clinical isolates were provided by Dr. Yuanqi Zhu. Next-generation sequencing was used to determine the resistance genes in each isolate, as described ( Feng et al, 2021 ). Eleven clinical A. baumannii strains harboring bla OXA-23 were selected.…”
Section: Methodsmentioning
confidence: 99%
“…SOAPdenovo2 was used to assemble the qualified reads. Glimmer was applied to predict the coding sequences, and the sequences were further compared against all known drug resistance genes using BLAST to obtain the types of resistance-encoding genes in all studied strains ( Feng et al, 2021 ). E. coli ATCC 25922 and A. baumannii ATCC19606 were selected as quality control strains for antimicrobial susceptibility tests.…”
Section: Methodsmentioning
confidence: 99%
“…A theory was postulated that the lesser time at which the bacteria spent in MSW would translate to a lesser opportunity for them to develop resistance ( Hesje et al, 2007 ). When MPC converged to MIC for all antibiotics in the combination, this suggests that there is no further resistance development ( Fedrigo et al, 2021 ; Feng et al, 2021 ). Two pharmacodynamic (PD) parameters are often used as an inference of the emergence of resistant mutants: ( Antunes et al, 2014 ) the fraction of time over the 24 h wherein the free drug concentration was within the MSW ( f T MSW ); and ( Maragakis and Perl, 2008 ) the fraction of time over the same period wherein the free drug concentration exceeds the MPC ( f T >MPC ).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1 , in vitro , aztreonam (≤0.03–4 μg/ml)+CAZ-AVI (4 μg/ml of the AVI component) exerts potent synergistic effects against most tested MBL-producing Enterobacteriaceae and few MBL-producing P. aeruginosa , which is superior to aztreonam alone or in combination with other drug combinations, such as aztreonam +amoxillin-clavulanate and aztreonam+ceftolozane-tazobactam (Emeraud et al, 2019 ; Niu et al, 2020 ; Khan et al, 2021 ; Maraki et al, 2021 ). With further research, the synergistic effect of aztreonam+CAZ-AVI on MBL producers was proven to be mainly caused by the combination of aztreonam and AVI (Feng et al, 2021 ). AVI is a novel β-lactamase inhibitor that effectively inhibits class A and C carbapenems (Das et al, 2019 ).…”
Section: Novel Antibiotics and β-Lactamase Inhibitors In Preclinical ...mentioning
confidence: 99%
“…A series of in vitro studies on the combined effects of aztreonam+AVI against MBLs have been carried out. Aztreonam+AVI (≤0.015–4+4 μg/ml) has strong antibacterial activity on Enterobacteriaceae producing MBLs alone or both MBLs and SBLs (Karlowsky et al, 2017 ; Biagi et al, 2019 ; Niu et al, 2020 ; Zhang et al, 2020 ; Bhatnagar et al, 2021 ; Cervino et al, 2021 ; Feng et al, 2021 ). Karlowsky et al found that aztreonam+AVI (4 μg/ml+4 μg/ml) also has a good inhibitory effect on a small portion of MBL- P. aeruginosa isolates (63/452) (Karlowsky et al, 2017 ).…”
Section: Novel Antibiotics and β-Lactamase Inhibitors In Preclinical ...mentioning
confidence: 99%